A 16-channel combined loop-dipole transceiver array for 7 Tesla body MRI - Ertürk, M. Arcan (Magn Reson Med, 2016)
PURPOSE: To develop a 16-channel transceive body imaging array at 7.0T with improved transmit, receive and SAR performance by combining both loop and dipole elements and utilizing their respective and complementary near and far field characteristics. METHODS: A 16-channel RF coil array consisting of eight loop-dipole blocks (16LD) was designed and constructed. Transmit and receive performance was quantitatively investigated in phantom and human model simulations, and experiments on five healthy volunteers inside the prostate. Comparisons were made with 16-channel microstrip-line (16ML) and 10-channel fractionated dipole antenna (10DA) arrays. The 16LD was used to acquire anatomic and functional images of the prostate, kidneys and heart. RESULTS: The 16LD provided >14% improvements in SNR, peak B(1)(+), B(1)(+) transmit and SAR efficiencies over the 16ML and 10DA in simulations inside the prostate. Experimentally, the 16LD had >20% higher SNR and B(1)(+) transmit efficiency compared to other arrays, and achieved up to 51.8% higher peak B(1)(+) compared to 10DA. CONCLUSION: Combining loop and dipole elements provided a body imaging array with high channel count and density while limiting inter-element coupling. The 16LD improved both near and far field performance compared to existing 7.0T body arrays and provided high quality MRI of the prostate kidneys and heart.